MAKNA KULTURAL DAN NILAI RELIGIUS TRADISI KEMBANG ENDOG-ENDOGAN DALAM PERINGATAN MULUDAN NABI DI BANYUWANGI - Agista Nora Kanahaya; Agus Machfud Fauzi; Diyah Utami (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Local religious traditions in Indonesia function not only as ritual practices but also as spaces for the production of social and religious meaning within community life. One such tradition is kembang endog-endogan, which is performed during the commemoration of the Prophet Muhammad's birthday (Maulid Nabi Muhammad SAW) in Kluncing Village, Licin District, Banyuwangi. This study aims to analyze the cultural meanings and religious values embedded in the kembang endog-endogan tradition and to examine its role in strengthening the social-religious identity of the local community. This research employs a qualitative descriptive approach using participant observation and in-depth interviews. Observations were conducted during the Maulid Nabi Muhammad SAW celebration around September 2025, while interviews involved eight informants consisting of religious leaders, community leaders, kembang endog artisans, and residents directly involved in the implementation of the tradition. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the kembang endog-endogan tradition contains religious symbolism representing the values of sharia, iman (faith), and ihsan through the interpretation of the egg's three layers. In addition, this tradition functions as a mechanism for strengthening social cohesion, transmitting religious values across generations, and reproducing the collective identity of the Banyuwangi community. Sociologically, these findings demonstrate that local cultural practices are capable of integrating Islamic teachings with local wisdom in a contextual manner and remaining relevant amid ongoing social change.